Biosyncretic Imaging Systems: Imaging with Optogenetically Engineered Living Cells as a Photodetector (Adv. Biosys. 8/2019). Issue 8 (14th August 2019) - Li, Gongxin; Wang, Feifei; Yang, Wenguang; Wang, Wenxue; Li, Guangyong; Wang, Yuechao; Liu, Lianqing
Abstract : In article number1800319, Wenxue Wang, Lianqing Liu, and co‐workers develop a biosyncretic imaging system integrating electromechanical devices with a cell‐based photodetector, which is established with an optogenetically engineered living cell. The imaging system successfully acquires high‐resolution images based on the compressive sensing theory. This work paves a new road for the development of future on‐body bionic devices.